Exit, voice, and loyalty: an analysis of African states' behaviour in relation to the international criminal court - Rubin, Maxine (Department of Political Studies, 2023)
African states have been divided in their relations with the International Criminal Court (ICC). Despite these divisions, the literature on this relationship has focused on withdrawal behaviour to the neglect of other types of behaviour, such as support for the ICC. Consequently, it is unable to explain what influences the diverse behaviour. This dissertation adapts Albert Hirschman's Exit, Voice, and Loyalty (EVL) model into an International Relations model to categorise the different types of behaviour by African states and, subsequently, guide an explanation of the behaviour. Primary evidence of each African State Party's official policy position toward the ICC consisted of 208 country statements delivered between 2008 and 2018 at relevant United Nations and ICC forums. The study used discourse analysis to interpret satisfaction and dissatisfaction with the ICC in the statements and, consequently, categorise the states into one of the three behaviour groups for each year and forum. The country statement data are complemented by key informant semi-structured interviews, academic literature, news articles, and grey literature to explain the major factors influencing the behaviour of each state. Five explanatory variables were prevalent as explanations of African states' behaviour in relation to the ICC – head of state interests, domestic factors, regional politics, reputational factors, and economic factors. It was found that behaviour was caused by combinations of these variables. Broadly, exit and voice were primarily influenced by head of state interest and regional politics, whereas loyalty was influenced by reputational factors and/or economic factors. The results of this study have important implications for the study of Africa's international relations. The findings about the influence of the head of state variable demonstrated the relevance of the personalisation of power and how this affects the production of foreign policy. The heterogeneity of behaviour also challenges the usefulness of ‘Africa' as a category and highlights issues of essentialism and reductionism with the treatment of ‘Africa' as an indivisible unit of analysis, at least, regarding the withdrawal debate.